THE IMPORTANCE OF GRAMMAR IN LANGUAGE LEARNING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article provides an in-depth exploration of the significance of grammar in language learning. It discusses how grammar serves as the backbone of effective communication, the cognitive processes involved in acquiring grammatical structures, and the impact of grammar on all four language skills: reading, writing, listening, and speaking. Special attention is paid to traditional and modern approaches to grammar teaching, communicative competence, and the integration of grammar instruction in various methods of language education. The article also reflects on the misconceptions about grammar learning, the role of grammar in shaping meaning and coherence, and its influence on cultural understanding. Finally, the article provides a comprehensive analysis of the practical and theoretical justifications for maintaining grammar as a central component in language education, supporting its claims with scholarly sources and contemporary research findings.
Keywords: grammar, language learning, communication, accuracy, syntactic structure, linguistic competence, language acquisition.